Calabar, o elogio da traição: um novo drama histórico - Lopez, Ana Cristina Caminha Viana (2006)
The teatral play Calabar, o Elogio da Traição, by Chico Buarque and Ruy Guerra, has for subject the historical episode of the Dutch Invasion in the BrazilColony of century XVII. The play focus the controversial historical character Calabar, intrepid warrior allied to portuguese, that, in 1632, desert for the dutch side. Instigating the reader/spectador to review history with other eyes, the authors of Calabar , using a mordacious irony, demystify the betrayal concept. Although belongs to the dramatical sort, Calabar, o Elogio da Traição is identified with the main characteristics of the literary subgenus of Latin American origin: the New Historical Romance (NHR). This work objective to realize a comparative and prospectus exercise: to transpose the model of the NHR to the Calabar work, as possibility of inclusion of this play in a possible model of the New Historical Drama. For in such a way, the work was divided in three chapters. In the first one, we approach some theoretical aspects and the passage of the literary subgenus “historical fiction” (including romance and drama) in the Romantism. We weave some comments about the NHR and the Brazilian drama of century XX. Finally, we display, our proposal of adaptation of the NHR’s characteristics to the Calabar play. In the second chapter, we revise the historical episode of the Dutch Wars and deal with the thematic appropriation of the Dutch Invasion in Brazilian Literature. In the third chapter, we realize the transposition process identifying the NHR’s characteristics in Calabar, O Elogio da Traição. Between them: critical revision, cyclical and unexpected character of history, rich intertextuality, parody, irony and metafiction.